Group Cohesiveness Among Employees: A Literature Review - Rizki Armeylia Nafica; Zahwa Shakira; Putry Rezty Aulya Nur (unprimdn.ac.id, 2026)
Modern organizations require employees who are able to collaborate effectively in teams, making group cohesiveness an essential aspect of human resource management. This study examines the factors that form group cohesiveness, its impact on performance, and strategies for improvement through a Systematic Literature Review (SLR) using the PRISMA procedure. The search was conducted on the Google Scholar database and yielded 1,400 initial articles, which were then selected through the identification stage, title and abstract screening, and full-text eligibility assessment, resulting in 30 articles published between 2021 and 2026 as the final units of analysis, with the 2026 cutoff referring to articles that were already available and accessible at the time of data collection. Each article that passed the eligibility stage was critically appraised based on the clarity of the method, the appropriateness of the sample, and the relevance of the results to the topic of group cohesiveness among employees, to ensure that only studies of adequate quality were included in the synthesis. The content analysis shows that group cohesiveness is positively correlated with work morale, job satisfaction, productivity, and Organizational Citizenship Behavior (OCB), and plays a role in reducing turnover intention and social loafing. The main factors influencing it include interpersonal communication, leadership, trust, and the work environment. Theoretically, this study enriches the understanding of work group dynamics within an organizational context. Practically, these findings can serve as a basis for designing managerial interventions to improve team effectiveness.